Pengaruh Kinerja Keuangan terhadap Alokasi Belanja Modal dan Pertumbuhan Ekonomi di Kabupaten/Kota Riau - Hygi Prihastuti, Asepma; Taufik, Taufeni; Agusti, Restu (Lembaga Penelitian dan Pengabdian kepada Masyarakat Universitas Riau, 2015)
Abstract Progress an area can be shown by good economic growth, in which one of the factors that influence economic growth is investment, the indicators is capital expenditure issued by local governments. Capital expenditure is also affected by whether or not the financial performance. This study aimed to determine the influence of regional financial performance impact allocation of capital expenditure and economic growth. Data analysis methods using Path Analysis with Partial Least Square (PLS) Program. The result of this study shown that financial performance influenced allocation of capital expenditure, allocation of capital expenditure did not influenced economic growth, financial performance influenced economic growth directly, and economic growth did not influenced by financial performance indirectly'